The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4018/ijcmhs.2018070101
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Dark Tourism

Abstract: This study looks at some primary points in the discourse of virtual dark tourism (VDT) formation. Derived from the spectrum of sound branding (SB), virtual reality (VR), coupled with augmented reality (AR), the case is used as a tool to support the claims of VDT. Findings suggest viewpoints for making death sites exclusive, and offer valuable clues to the design of VDT formation as an option to include death sites as market offerings of dark tourism. Guided by social constructionist research philosophy, couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Kellaris and Kent (1992) found that time appears to move more slowly in music with a major key, which would appear to support the notion of slow tourism perceptions (Oh et al, 2016). Minor keys tend to be associated with negative emotion, particularly since they have learned associations with funerals and other grief-stricken contexts, dysphoria, and sad imagery (Handayani & Korstanje, 2018). On the other hand, major keys tend to be associated with positive emotions such as joy, happiness, hope, and triumph (Hevner, 1935).…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%
“…Kellaris and Kent (1992) found that time appears to move more slowly in music with a major key, which would appear to support the notion of slow tourism perceptions (Oh et al, 2016). Minor keys tend to be associated with negative emotion, particularly since they have learned associations with funerals and other grief-stricken contexts, dysphoria, and sad imagery (Handayani & Korstanje, 2018). On the other hand, major keys tend to be associated with positive emotions such as joy, happiness, hope, and triumph (Hevner, 1935).…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%